Consensus report on therapeutic drug monitoring of mycophenolic acid in solid organ transplantation - Kuypers, Dirk; Meur, Yannick Le; Cantarovich, Marcelo; Tredger, Michael J.; Tett, Susan E.; Cattaneo, Dario; Tönshoff, Burkhard; Holt, David W.; Chapman, Jeremy; Gelder, Teun van (Clinical journal of the American Society of Nephrology, 2010)
With the increasing use of mycophenolic acid (MPA) in solid organ transplantation, the need for more accurate drug dosing has become evident. Personalized immunosuppressive therapy requires better strategies for avoidance of drug-related toxicity while maintaining efficacy. Few studies have assessed the clinical usefulness of therapeutic drug monitoring (TDM) of MPA in solid organ transplantation in a prospective way, and they have produced opposing results. To provide clinicians with an objective and balanced clinical interpretation of the current scientific evidence on TDM of MPA, a consensus meeting involving 47 experts from around the world was commissioned by The Transplantation Society and held in Rome on November 20 to 21, 2008. The goal of this consensus meeting was to offer information to transplant practitioners on clinically relevant pharmacokinetic characteristics of MPA, to rationalize the basis for currently advised target exposure ranges for MPA in various types of organ transplantation, and to summarize available methods for application of MPA TDM in clinical practice. Although this consensus report does not evaluate the final role of MPA TDM in transplantation, it seeks to examine the current scientific evidence for concentration-controlled dosing of MPA.
Gesehen am 09.03.2023
DOI funktioniert nicht